Methodology development and integrated control power-speed high-class handball players - Josan, I. A.; Strikalenko, E. A.; Shalar, O.G. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose : based practices and identify effective means of controlling the level of development of power-speed high-class handball players. Material : The study involved 24 women’s handball team player of Super League of Ukraine "Dneprjanka" Kherson. Results : methodical conditions defined development speed-strength. Revealed significant changes in terms of the development of power-speed after applying the proposed method of training. Hit run handball throws the ball with 7 meters at best point guards (4.9 ball) and welterweight (4.6 ball) players, and the lowest at the extremes (4.4 ball) and linear (4.4 ball) players. Analyzing the accuracy of the shots from a 9-meter mark, found no significant differences between the mean values are not established. Conclusions : Exercise speed-strength of character necessary to carry out the preparatory and in the early part of the basic training. Handball is recommended to use individual tasks to improve the general and special speed-strength training.